Assessment of lipid synthesis from sugarcane biomass by adaptive strains of Rhodosporidium toruloides - de Almeida, Sâmilla Gabriella Coelho [UNESP]; Souza, Jonas Paulino [UNESP]; Fogarin, Henrique Maziero [UNESP]; Franca, Bruno Valente [UNESP]; Dussán, Kelly Johana [UNESP] (Springer Nature, 2024)
Rhodosporidium toruloides is an unconventional yeast with a natural lipid pathway known to accumulate oil under suitable conditions, typically characterized by nutritional stress induced through the depletion of essential nutrients. The objective of this research was to evaluate microbial oil production by implementing an adaptation strategy in three strains of Rhodosporidium toruloides, all isolated from the Brazilian biome, to increase tolerance to degradation products resulting from pretreatment steps of sugarcane biomass. This is the first time these three strains have been tested for lipid accumulation and tolerance to biomass hydrolysate. The assays were performed to study the assimilation of glucose and xylose, as well as the performance of their mixture in synthetic medium. Subsequently, all non-adapted strains were tested using the previously obtained non-detoxified hemicellulosic hydrolysate. Due to their performance, a step of previous adaptation of the media was employed. Essentially, the strains were successive cultivated in increasing concentrations of hemicellulosic hydrolysate, incremented by 10% every 24 h until reaching 100% hydrolysate. Microbial oil production and yeast growth in the hemicellulosic hydrolysate were compared for the adapted and non-adapted strains. The results indicate that lipid accumulation was enhanced through fermentation of the adapted strain, resulting in improvements of 1.69, 2.51, and 2.84 times compared to the non-adapted strain for R. toruloides 2781, R. toruloides 2882, and R. toruloides 2896, respectively. Overall, the adapted strain R. toruloides 2896 showed the best performance, with a productivity of 16.6 ± 0.63 mg.L−1.h−1. This study introduces an improved approach to microbial oil production from biowaste and highlights the detrimental impact of toxic compounds in the medium, leading to the inhibition of cellular fermentative performance, especially noticeable in non-adapted strains. Conversely, adapted strains exhibited increased tolerance to specific toxic compounds in hemicellulosic hydrolysate, particularly towards acetic acid and components such as acid-soluble lignin. Notable constituents include syringaldehyde, gallic acid, 2,4-dihydroxybenzoic acid, and the furanic compound furfural. This heightened comprehension may yield insights that contribute to the advancement of knowledge in this field of study.
Keywords: Adapted strain; Fermentation; Lignocellulosic biomass; Microbial oil; Oleaginous yeasts